(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Waste water from different processing industries such as paper, textile, etc. contributes substantial environmental problems because it contains huge amounts of colored contaminants. The colour compounds include dyes or their by-products which do not meet regulatory standards for waste water discharge even after it has undergone treatment by a conventional process. Various processes have been utilized to remove such organic pollutants and to reduce their associated high biological oxygen demand. As the resourcesof water have been getting exposed to different types of contaminants, the whole food chain is getting adversely affected. Their toxicity, constancy to natural degradation and prolonged perseverance in the environment has been the major reason for their accumulation. Some of the recent issues associated with the release of effluents in the environment comprise green house effect, etc.Because of the extensive use of chemicals, such as dyes and colors, the processing of textiles consequences in group of large measures of extremely contaminatedcoloured waste water. The dyes and dye intermediates used in the textile industry have high toxicity and low biodegradability. It is estimated that about 10- 15% of the dyes goes as industrial waste. During the processing of textiles, huge quantities of wastewater generated having high pH and high attentiveness of organic compounds which are non-biodegradable matter and toxic, is generated. This effluent causes thoughtful influences on usual water bodies and land in the nearby area.As a consequence, textile manufacturing is challenged with the test of together colour elimination and degradation of the dyes that exist in the waste water. For the effluent generated in textile industries, majority of the dyes which are being used for dyeing are persistent in nature, thus polluting the environment. The azo dyes and reactive dyes like Malachite green, Methylene blue, Reactive blue and Reactive orange, etc. are the most regularly used dyes. Colour removal from the textile wastewater upto this specified absorbance limit has become an issue of interest also because of the toxicity of dyes and the coloured effluent from the textile industries affects the appearance of water.